Ibn Hajars assessment of Ijma in his book (Fath Al-Bari) - Alzarooni, Mohamed Saddiq Hajouni (2021)
The thesis aims to know the most prominent views of Imam Ibn Hajar al Asqalani in matters of fundamentalist consensus, and to trace his trackbacks on the jurisprudential (Fiqh) issues in the chapters of worship through his book Fath al- Bari with the Explanation of Sahih al-Bukhari, and to study them according to the inductive, analytical and critical method to verify the authenticity of these trackbacks and knowing his resources in them. The study has fulfilled its questions and aims, and the researcher has reached conclusions, the most important of which is the affirmation of the reputability of Imam Ibn Hajar, his wide knowledge, and the diversity of his sources in his tracks. Also the study included extrapolating the traces of Ibn Hajar in the chapters of worship and counting them, then judging the validity or lack of the tracking. The researcher recommends, at the end of his research, more studies that take care of the trackbacks of Imam Ibn Hajar and other scholars on various legal and Fiqh issues.